Analysis of judge's decision number 44/PDT.P./2023/PA.BN regarding dispensation of marriage due to pregnancy outside of marriage in the perspective of the Marriage Law - Seli Lorenza; Ferawati Royani; Dwi Putra jaya; Hurairah Hurairah (JURNAL HUKUM SEHASEN, 2023)
Marriage is a living union between a man and a woman which is formally confirmed by law, namely juridical and mostly also religious according to husband and wife goals and law. Article 103 states that husband and wife must be loyal to each other, help each other and help each other. The formulation of the problem in this study is how to apply and consider judges in deciding Decision Number 44/PDT.P/2023/PA.BN regarding marriage dispensation from a legal perspective. The legal research method used is normative, normative legal research (legal research) is a document study, legal marital status is one of the things that women especially want, considering that in marriage there are absolute rights for women and men that are guaranteed or protected. by the state based on applicable law. In Indonesia, the majority of marriages are carried out by minors. Marriage dispensation is necessary, but on the other hand there are also negative impacts, namely the existence of marriage at an early age or not old enough, it will increase the divorce rate and can increase the unemployment rate and abandoned children. There are several factors that influence the occurrence of underage marriages or the occurrence of marriage dispensation, namely economic factors, educational limitations, dropping out of school or not going to the same school, and social factors of marriage.